“Breeder of Feral Worlds,” or the End of the World as a Movable Feast - Kot, Radosław (Sensus Historiae, 2024)
The text discusses an article about the so-called “quantum cat breeding,” which is a concept related to the areas of quantum physics and imaginescopy. It focuses especially on the process of the so-called “breeding of worlds,” particularly on the specific case of breeding (multiplying) feral worlds as an attempt to explain the growing information chaos, mainly in the network area (with particular emphasis on social media), but with important references to the physical world.